Metanalysis on the effectiveness of low back pain treatment with oxygen-ozone mixture: Comparison between image-guided and non-image-guided injection techniques. (2021) - Rimeika, Gustas; Saba, Luca; Arthimulam, Ganesan; Della Gatta, Luigi; Davidovic, Kristina; Bonetti, Matteo; Franco, Donatella; Russo, Camilla; Muto, Mario
Abstract: Low back pain (LBP) is a common disorder affecting an increasing number of people worldwide, whose diagnosis is focused on the identification of triggering causes. First line therapy usually starts from conservative approaches, whereas second line treatments include a spectrum of minimally invasive techniques, before resorting to more invasive surgical approaches. Among minimally invasive techniques, percutaneous oxygen-ozone injections represent one of the most common and cost-effective procedures. Aim of this study is to provide a metanalysis on literature evidences on percutaneous oxygen-ozone injections, comparing image-guided to non-image-guided techniques for LBP treatment. Imaging-guided procedures showed better performances compared to non-image-guided techniques based only on anatomical landmarks, with higher therapeutic efficacy and lower age-related variability in clinical results. Highlights: Low back pain (LBP) is a common spine disease and one of the most frequent causes of absence from work in developed countries. In case of conservative approaches failure, minimal invasive techniques can be envisaged as second line therapies in LBP. Percutaneous oxygen-ozone injections are one of the most cost-effective procedures. Imaging-guided ozone therapy showed higher therapeutic efficacy and lower age-related variability compared to non-image-guided techniques based on anatomical landmarks.